2016
DOI: 10.1089/apc.2015.0349
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric Network and Condom Use Among Mid-Age Female Sex Workers in China: A Multilevel Modeling Analysis

Abstract: The epidemics of sexually transmitted infections (STIs) have spread among older adults in the world, including China. This study addresses the deficiency of studies about the multiple contextual influences on condom use among mid-age female sex workers (FSWs) over 35 years old. A combination of an egocentric network design and multilevel modeling was used to investigate factors of condom use over mid-age FSWs (egos) particular relationships with sexual partners (alters). Of the 1245 mid-age FSWs interviewed, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…Egocentric analysis is particularly useful for understanding relationship patterns, social structures, and the influence of an individual’s social network on his or her behavioral outcomes. This approach has been used extensively to understand interpersonal communications (Barrington et al, 2009; Fisher, 2005; Koehly et al, 2003; Tillema et al, 2010) and health behaviors (De et al, 2007; Huang et al, 2014; Liu, 2016). Although egocentric network analysis is dominated by quantitative research methods, qualitative methods are also valid approaches when the intention of the investigation is to explore the subjective meaning of social network members and to generate hypotheses (Fuhse & Mützel, 2011; Scott & Carrington, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Egocentric analysis is particularly useful for understanding relationship patterns, social structures, and the influence of an individual’s social network on his or her behavioral outcomes. This approach has been used extensively to understand interpersonal communications (Barrington et al, 2009; Fisher, 2005; Koehly et al, 2003; Tillema et al, 2010) and health behaviors (De et al, 2007; Huang et al, 2014; Liu, 2016). Although egocentric network analysis is dominated by quantitative research methods, qualitative methods are also valid approaches when the intention of the investigation is to explore the subjective meaning of social network members and to generate hypotheses (Fuhse & Mützel, 2011; Scott & Carrington, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Partner characteristics may influence STI transmission within these sexual networks. For example, previous studies have shown that individuals are less likely to consistently use condoms with trusted partners or partners who provide emotional support, 14 Furthermore, condom use negotiation among gay men and other MSM varies according to partner characteristics, with the insertive partner being more likely to determine condom use than the receptive partner, 15 Understanding network factors associated with STI acquisition is of public health importance because GC, CT, and HIV infections may act synergistically to facilitate onward transmission. For example, ulceration and inflammation resulting from GC or CT increases individual susceptibility for HIV acquisition, 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Social network research may provide new evidence regarding the constitution of mid-age FSWs’ networks, interactions between egos and alters, and diffusion of social influences. The findings from our qualitative and quantitative studies in the same study population have documented that engagement in risk behavior for HIV infection was influenced by network factors and social support was positively associated with condom-protected sex (36, 37). …”
Section: Introductionmentioning
confidence: 68%
“…The study methods have been previously described in detail (36, 45) The study protocol was approved by the Institutional Review Boards of the University of Maryland, Shandong University School of Public Health, and the Centers for Disease Control and Prevention in Hefei and Guangxi. Written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%